myWorld history - Karpiel, Frank; Krull, Kathleen (Pearson, 2012)
Unit 1. Origins -- Unit 2. The ancient Near East -- Unit 3. Ancient India and China -- Unit 4. Ancient Greece -- Unit 5. Ancient Rome -- Unit 6. The Byzantine Empire and Islamic civilization -- Unit 7. African and Asian civilizations -- Unit 8. Civilizations of the Americas -- Unit 9. Europe in the Middle Ages -- Unit 10. The rise of Europe.